Program For Developing Rural Area Elementary School Teachers Professionalism Based on TPACK: Review Empirical And Reflective - Abror Huda, Tiyas; Yayah Haenilah, Een; Abdurrahman (Program Doktor Pendidikan FKIP Universitas Lampung, 2023)
This study aims to develop the professionalism of rural area elementary school teachers based on TPACK. The subject of this research is the Teacher Professional Education (PPG) Participants at the University of Lampung in 2020 in the field of study for elementary school teachers from rural areas in Lampung Province. The research sample amounted to 49, which were determined purposively. This study uses qualitative research with a Narrative Study Approach. The focus of this research is to produce a hypothetical model that can overcome the obstacles of PPG participants from rural areas so that it can be a solution to increase professionalism while supporting UKMPPG Graduation. Data collection techniques are used in the form of questionnaires, interviews and documents. The results showed that PPG participants were proven to have problems in the form of weak internet signals and a lack of mastery of technology, which impacted their unpreparedness to participate in PPG in terms of technology and content. Based on these conditions, the hypothetical model includes three scaffolding levels. Thus, theoretically, scaffolding can develop teacher professionalism.